A Dedifferentiation Strategy to Enhance the Osteogenic Potential of Dental Derived Stem Cells - Paduano, Francesco; Aiello, Elisabetta; Cooper, Paul Roy; Marrelli, Benedetta; Makeeva, Irina; Islam, Mohammad; Spagnuolo, Gianrico; Maged, Davide; De Vito, Danila; Tatullo, Marco (Frontiers in Cell and Developmental Biology, 2021)
Dental stem cells (DSCs) holds the ability to differentiate into numerous cell types. This property makes these cells particularly appropriate for therapeutic use in regenerative medicine. We report evidence that when DSCs undergo osteogenic differentiation, the osteoblast-like cells can be reverted back to a stem-like state, and then further differentiated toward the osteogenic phenotype again, without gene manipulation. We have investigated two different MSCs types, both from dental tissues: dental follicle progenitor stem cells (DFPCs) and dental pulp stem cells (DPSCs). After osteogenic differentiation, both DFPCs and DPSCs can be reverted to a naïve stem cell-like status; importantly, dedifferentiated DSCs showed a greater potential to further differentiate towards the osteogenic phenotype. Our report aims to demonstrate for the first time that it is possible, under physiological conditions, to control the dedifferentiation of DSCs, and that the rerouting of cell fate could potentially be used to enhance their osteogenic therapeutic potential. Significantly, this study first validates the use of dedifferentiated DSCs as an alternative source for bone tissue engineering.